High performance Li-ion capacitor fabricated with dual graphene-based materials. (19th October 2020) - Sui, Dong; Wu, Manman; Liu, Yiyang; Yang, Yanliang; Zhang, Hongtao; Ma, Yanfeng; Zhang, Long; Chen, Yongsheng
Abstract: Lithium-ion capacitors (LICs) are now drawing increasing attention because of their potential to overcome the current energy limitations of supercapacitors and power limitations of lithium-ion batteries. In this work, we designed LICs by combining an electric double-layer capacitor cathode and a lithium-ion battery anode. Both the cathode and anode are derived from graphene-modified phenolic resin with tunable porosity and microstructure. They exhibit high specific capacity, superior rate capability and good cycling stability. Benefiting from the graphene-enhanced electrode materials, the all graphene-based LICs demonstrate a high working voltage (4.2 V), high energy density of 142.9 Wh kg −1, maximum power density of 12.1 kW kg −1 with energy density of 50 Wh kg −1, and long stable cycling performance (with ∼88% capacity retention after 5000 cycles). Considering the high performance of the device, the cost-effective and facile preparation process of the active materials, this all graphene-based lithium-ion capacitor could have many promising applications in energy storage systems.